Higher education and human capital re/thinking the doctorate in America - Callejo-Pérez, David M. 1972-; Fain, Stephen M. 1940-; Slater, Judith J. (SensePublishers, 2011)
This book attempts to re-imagine the purpose of the doctorate, which has historically been used to prepare leaders who will work to improve the sciences (social and physical), humanities, and professions, while articulating curriculum as a living shape where students, faculty, and institution melded in a humanist and creative process. This idea, seriously eroded by the explosion in doctoral degrees between the early 1970s (20,000 doctorate per year) and last year (to over 46,000)-and an explosion in doctoral and research universities that has created a crossroads for the doctorate in America. We believe the value of a doctorate is Intellectual Capital, and are particularly interested in encouraging reflection as an important characteristic of a successful quality doctoral program. We posit that a 'good doctoral' experience fosters active engagement in reflection on all elements of our work-the intellectual, advisory, and pedagogical work of faculty, curricular opportunities, as well as the intellectual of the doctoral candidates through an avocation that drives research and theory in our fields. Specific issues raised in this edited volume include comprehensive analysis of programs, rethinking evaluation and programmatic coherence, doctoral degrees beyond the discipline, subject, and field, and implications of individual identity. Along with authors' chapters, we paid attention to encourage reflection as an important characteristic of a quality doctoral program; positing that 'good doctoral' experiences foster active engagement in reflection on all elements of the doctoral experience, including program and curricular issues, personal relationships, work, and the creation of a community of scholars